Prevalence and Correlates of Psychiatric Problems among Engineering Students - Pandey, AK; Adhikari, BR; Verma, SK; Bhojak, MM (Journal of Universal College of Medical Sciences, 2014)
INTRODUCTION: Mental health among students represents an important and growing public health concern. College is a place where student learns new experiences which play a vital role in physical as well as psychological growth for the identity consolidation. Engineering students experience frequent psychological distress as of various underlying reasons leading to psychiatric disorders including anxiety, depression, substance use etc. MATERIAL AND METHODS: The final sample consisted of 196 students (1st year 50, 2nd year 51, 3rd year 48 and final year 47) from the Malviya National Institute of Technology (MNIT) Jaipur, the premier engineering college of Rajasthan, India. Study was conducted in two phases. In first phase, engineering students were administered socio-demographic data sheet and GHQ-60 (General Health Questionnaire) hindi version to ascertain the extent of psychiatric illnesses. False positive cases were dropped and in second phase the diagnosed students with psychiatric problems and control group were individually administered a battery of tests to determine the role of various possible causative factors. Scores obtained on different measures were arranged as per the requirement of research design and statistical procedure. RESULTS: Out of all the subjects, 24.49% had some psychiatric disorders. Psychiatric disorder was highest i.e. 32% in 1st year students and overall in 36.60% of female students. Statistically significant differences were noted on various applied tools. CONCLUSION: Students who had higher scores on GHQ-60 scale had more neurotic problems, poor coping skills and abnormal personality traits and had high psychiatric morbidity than the vice versa group. DOI: http://dx.doi.org/10.3126/jucms.v2i2.11167 Journal of Universal College of Medical Sciences (2014) Vol.2(2): 6-10